2008
DOI: 10.1161/circulationaha.107.706127
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Risk of Cardiovascular Disease

Abstract: Background-Vitamin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
1,558
13
67

Year Published

2010
2010
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 2,147 publications
(1,690 citation statements)
references
References 63 publications
52
1,558
13
67
Order By: Relevance
“…This is in line with prospective population-based studies which showed that low 25(OH)D levels are an independent risk factor for cardiovascular events and cardiovascular mortality [101][102][103]. We are aware that discussing the causality of vitamin D deficiency for chronic diseases is a difficult task because sun exposure is the main determinant of vitamin D status and is usually inversely correlated with the severity of illness.…”
Section: Clinical Consequences and Summarysupporting
confidence: 77%
“…This is in line with prospective population-based studies which showed that low 25(OH)D levels are an independent risk factor for cardiovascular events and cardiovascular mortality [101][102][103]. We are aware that discussing the causality of vitamin D deficiency for chronic diseases is a difficult task because sun exposure is the main determinant of vitamin D status and is usually inversely correlated with the severity of illness.…”
Section: Clinical Consequences and Summarysupporting
confidence: 77%
“…Many reports Karasik et al 2002) have documented a decrement in IGF1 plasma levels with age in humans. (Wang et al 2008), and cancers of the breast, colon, and prostate (Martinez et al 1996;Garland et al 1989;John et al 1999). A recent meta-analysis of randomized controlled trials suggested that vitamin D supplementation led to significant reductions in mortality (Autier and Gandini 2007).…”
Section: Biochemical and Endocrine Serum Markersmentioning
confidence: 99%
“…Low vitamin D levels are associated with a higher risk of developing type 2 diabetes [4], worse glycaemic control in type 2 diabetes, higher serum lipid levels and a higher prevalence of cardiovascular disease [3]. Low vitamin D levels are also associated with an increased risk of hypertension and cardiovascular events in population-based studies [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%